1981
DOI: 10.1210/endo-108-5-1658
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary and Gonadal Gonadotropin-Releasing Hormone Receptors during Sexual Maturation in the Rat*

Abstract: The gonadotropin-releasing hormone (GnRH) agonist D-Ala 6 -des-Glyio-GnRH ethylamide (D-Ala analog) was used as ligand to study GnRH receptors in the pituitary and gonads during sexual maturation in the rat. The affinities of the GnRH receptor (Ka = 6.5 x 10 9 M" 1 ) were similar in all three tissues and did not change during maturation. Pituitary GnRH receptor concentration increased 2-fold in both sexes. Peak values occurred earlier (20 days) and were higher (720 ± 52 fmol/ mg protein) in females than in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 39 publications
10
37
1
Order By: Relevance
“…The dilution of GnRH in the portal vessels may, thus, have driven the evolution of the more compact GnRH with higher affinity binding. However, some of the earlier-evolved functions seen in protochordates appear to have been retained in vertebrates as GnRH and GnRH receptors are present in the gonads of fish, amphibians, and mammals (5-7), suggesting direct effects on gonads (40).…”
Section: Discussionmentioning
confidence: 99%
“…The dilution of GnRH in the portal vessels may, thus, have driven the evolution of the more compact GnRH with higher affinity binding. However, some of the earlier-evolved functions seen in protochordates appear to have been retained in vertebrates as GnRH and GnRH receptors are present in the gonads of fish, amphibians, and mammals (5-7), suggesting direct effects on gonads (40).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ojeda et al (1977) found that the infantile female rat is more sensitive to GnRH compared with the neonatal and juvenile rat. Dalkin et al (1981) observed a sharp peak in GnRH receptor density in the pituitaries of female infantile rats. However, during this development stage male pituitaries showed only a discrete increase in GnRH-binding capacity, and the largest receptor density was observed in 30-day-old rats (Dalkin et al 1981).…”
Section: Introductionmentioning
confidence: 88%
“…Dalkin et al (1981) observed a sharp peak in GnRH receptor density in the pituitaries of female infantile rats. However, during this development stage male pituitaries showed only a discrete increase in GnRH-binding capacity, and the largest receptor density was observed in 30-day-old rats (Dalkin et al 1981). Also, it has been shown that infantile male pituitary gonadotrope cells are heterogeneous, with a significant population of small cells (Denef et al 1978 as in the female pituitary (Denef et al 1978), and also they exhibit an irregular shape and a high nucleo-cytoplasmic ratio .…”
Section: Introductionmentioning
confidence: 88%
“…This is paralleled closely by an increased pituitary LH content (Chan et al, 1981 (Chan et al, 1981;Dalkin et al, 1981). The decline in GnRH receptor concentration is mirrored by increasing serum testosterone concentrations, suggesting that an increased negative feedback action of gonadal hormones may cause a reduction in GnRH receptors either secondary to an inhibition of endogenous GnRH secretion (Chan et al, 1981) or by a direct inhibitory action of testosterone on the gonadotrophs (Giguere, Lefebvre & Labrie, 1981 (Döhler & Wuttke, 1975;Chan et al, 1981;Dalkin et al, 1981).…”
Section: Male Ratsmentioning
confidence: 95%
“…The decline in GnRH receptor concentration is mirrored by increasing serum testosterone concentrations, suggesting that an increased negative feedback action of gonadal hormones may cause a reduction in GnRH receptors either secondary to an inhibition of endogenous GnRH secretion (Chan et al, 1981) or by a direct inhibitory action of testosterone on the gonadotrophs (Giguere, Lefebvre & Labrie, 1981 (Döhler & Wuttke, 1975;Chan et al, 1981;Dalkin et al, 1981). The concentrations of serum FSH, as in male rats, rise characteristically between Days 10 and 20 of age with a peak value at Day 15 (Ojeda et al, 1980;Chan et al, 1981;Dalkin et al, 1981 (Debeljuk et al, 1972b;Ojeda, Jameson & McCann, 1977;Dullart, 1977 (Chan et al, 1981), since the latter remained constant after 30 days of age. Before this time high concentrations of a-fetoprotein in serum cause elevated total serum oestradiol concentrations in female rats.…”
Section: Male Ratsmentioning
confidence: 99%